Could the infiltration of the thyroarytenoid muscle define the pT2 glottic carcinoma?. Issue 10 (5th August 2019) - Lionello, Marco; Bertolin, Andy; Nardello, Ennio; Giacomelli, Luciano; Canal, Fabio; Rizzotto, Giuseppe; Marioni, Gino; Lucioni, Marco
Abstract: Background: The involvement of the thyroarytenoid (TA) muscle by glottic cancer may be related to an impaired vocal cord mobility, which is classified as cT2 disease. The primary endpoint was to evaluate the prognostic significance of TA muscle involvement in early glottic cancer treated with transoral laser microsurgery (TLM). Methods: A review was conducted on a cohort of 209 patients consecutively treated with TLM for early glottic carcinoma. Univariate analysis was used to examine the prognostic meaning of clinical and pathological parameters. Results: The statistical analysis showed that TA muscle infiltration correlated significantly with a worse prognosis in terms of recurrence rate and disease‐free survival, and this was confirmed even in the subcohort with pT1a glottic cancer. Conclusions: Our preliminary findings suggest that it could be considered as a criterion for upstaging a glottic cancer from pT1 to pT2.